A Themed Issue in Memory of Academician Zhu Yingguo (1939-2017) - Zhu, Yuxian; Li, Shaoqing; He, Guangcun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Professor Yingguo Zhu, an Academician of the Chinese Academy of Engineering, devoted his whole life (1939-2017) with tremendous enthusiasm to breeding hybrid rice. He studied and worked at Wuhan University for 58 years and contributed to enriching the diversity of hybrid rice, such as Maxie-type and Honglian-type hybrid rice. We are organizing this Special Issue in his honor to remember his great contributions to hybrid rice, especially Honglian-type male sterility. We invite researchers, including his former students, to submit manuscripts focused on male sterility, rice breeding, and, in particular, hybrid rice breeding, functional genomics research, gene mining and utilization, transposons, and the creation of germplasm. In addition, new technology and cutting-edge research studies are also welcome. We believe that this Special Issue will be helpful to the research on rice and the improvement of hybrid rice breeding in the future.